CCAFS Outcome Synthesis Report: Outcomes Achieved Within the Context of Climate-Smart Village Approach - Beal, Catherine; Bernardo, Eisen; Castellanos, Andrea Estefania; Martínez, Jesús David; Ouédraogo, Mathieu; Recha, John W.M.; Radeny, Maren A.O.; Shirsath, Paresh B.; Läderach, Peter R.D.; Bonilla-Findji, Osana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This working paper aims to assess outcome cases related to the AR4D Climate-Smart Village (CSV) approach. It presents results from a review of annual outcome case studies reported under the CCAFS program between 2012-2020. This review focused on outcomes directly related to the implementation of the CSV approach as well as those that took place within the context of CSV work or were informed by evidence generated in the CSV specifically aimed to address the following key questions: 1. What types of outcomes based on CSV related work were achieved? What changed in the next user? 2. How were these outcomes achieved? What was crucial to the change in next users? What key partners were involved?